Prophet Yusuf (as): the archetype of chastity - Ahmed, Zakir; Osmani, Noor Mohammad (IIUM Press, 2022)
When Prophet Muḥammad (PBUH) was asked about the noblest person on earth, he responded: “The noble, son of the noble, son of the noble, son of the noble, Yūsuf bin Yaʿqūb bin Isḥāq bin Ibrāhīm.” Born into a house of prophets and messengers—Yūsuf (AS) was destined to carry on the blessed legacy of his noble forefathers. Unlike any other sūrah in the Qurʾān, Sūrah Yūsuf contains the longest sustained story revolving around one personality—Yūsuf (AS). Stories of prophets and messengers are found throughout the Qurʾān, but the story of Yūsuf (AS) is concentrated entirely in this sūrah. In addition, the story is presented in a chronological manner highlighting major events in Yūsuf’s (AS) life—from youthhood to prophethood to government. It is important to note that the sūrah contains timeless lessons for all age groups and dynamics. The research adopts descriptive, historical and analytical approaches while presenting the model of Prophet Yousuf for the youths of today. The research presents Yūsuf (AS) as the archetype of chastity and further presents practical lessons for contemporary youth from his noble example.